Impact of in-Station Medication Automated Dispensing Systems on Prehospital Pain Medication Administration. (3rd April 2023) - Gaither, Joshua B.; Rice, Amber D.; Jado, Isrealia; Armstrong, Smita; Packard, Samuel E.; Clark, John; Draper, Scott; Duncan, Mike; Bradley, Brad; Spaite, Daniel W.
Abstract: Introduction: Medication automatic dispensing systems (ADS) have been implemented in many settings, including fire-based EMS stations. The aim of this study was to evaluate the impact of in-station ADSs on controlled substance administration rates and EMS response intervals. Methods: This study was a retrospective review of data from a single fire-based EMS agency. Medication administration rates and EMS response intervals were compared before ADS implementation (P1; 6/1/15 to 5/31/16) and after ADS implementation (P3; 6/1/17-5/31/19). Cases with missing data and during a one-year implementation period were excluded. Results: 4045 cases were identified in P1 and 8168 in P3. The odds of morphine or versed administration increased following ADS implementation: OR = 1.77 (95% CI: 1.53, 2.03) and OR = 1.53 (95%CI: 1.18, 2.00) respectively. There were statistically, but likely not operationally significant increases in median response interval and transport interval from P1 to P3 of 14 seconds, (p < 0.001) and 39 seconds (p < 0.001) respectively. Time at hospital for all calls decreased by more than 11 minutes for all transports, from a median of 34 minutes (IQR; 23.7, 45.5) to 22.7 minutes (IQR:18.5, 27.6) in P3, p < 0.001 and by 27.9 minutes for calls in which a controlled substance was given: P1 = 50.6 minutes (IQR: 34.6, 63.2), P3 = 22.7 minutes (IQR: 18.3, 27.4), p < 0.001. Conclusion: In this system, medication ADS implementation was associated with an increase in the rates of controlled substance administration and a decrease in the time units were at hospitals.